Enhancing topic-specific prior knowledge of students impacts their outcomes in mathematics - Alreshidi, Nawaf Awadh Khallaf (Frontiers in Education, 2023)
The aim of this study was to investigate how enhancing topic-specific prior mathematical knowledge of students before introducing new topics impacts their outcomes in mathematics achievements. A quasi-experimental design was applied to two groups: a control group (students who did not receive enhancement for their topic-specific prior mathematical knowledge (N=37)) and an experimental group (students who received enhancement for their topic-specific prior mathematical knowledge (N=36)). The results revealed that there were no significant differences between the students’ average scores in ‘conceptual knowledge’ in the immediate post-test for groups; however, the difference was significant in the delayed post-test in favour of the experimental group. The results also showed that there were significant differences between the students’ average scores in ‘procedural knowledge’ in both the immediate and delayed post-tests in favour of the experimental group. The implications of the study are discussed.